Mutations Driving Breast Cancer: A Comprehensive Review of Genetic Alterations (Asian Journal of Pharmaceutics (AJP), 2024)
The abstract of the paper on gene mutations in breast cancer presents several key points regarding the disease’ssignificance and underlying genetic mechanisms: Breast cancer is identified as a major public health issue anda leading cause of cancer-related deaths among women globally. This highlights the urgency of addressing thedisease through research and treatment strategies. The paper notes that various genes and their mutations havebeen linked to breast cancer. Despite the complexity of the disease, advancements in research techniques haveallowed for the identification of these genetic factors, which are crucial for understanding breast cancer’s etiology.The development of breast cancer is described as a multifaceted process influenced by hormonal, dietary, andgenetic components. This complexity necessitates a comprehensive approach to prevention and treatment.